Western and Arabic Islamic Architecture Discourse - Al-Akkam, Akram Jassim (Iraqi Journal of Architecture and Planning, 2009)
Many literatures concentrated on the issue of architecture discourse which identified by the space of conceptual thought that has essential characteristics based on knowledge foundations and distinctive historical, cultural, religious, and social dimensions. These literatures pointed to westem architecture discourse elements and Arabic Islamic architecture discourse and cultural, environmental and doctrinal reference, But these literatures didn’t present clear comparative picture for those discourses. The aim of current investigation is to conduct a comparison between those discourse elements, it hypothesized a variation between their structural foundations. To achieve the study aim, the research depended on intensive theoretical literature review. The results demonstrated, the variation of discourses at almost all elements which include, the view toward human existence in cosmos, the method of understanding of metaphysical world, the nature of human, reference ofdiscourse and its nature, discourse dependencies, objectives and characteristics, the mechanism of conceptual thought, discourse building and types, interest and concentrating approaches, method of embodiment, research topics, the nature of viewing aesthetics and aesthetic values production methods and rules, spatial perception, viewing creating. architecture as a culture and its reference origins, contemporarization and originality, theory and practice, spatiality of evaluation criteri4 expression and meaning and their tools, spatial correlation and surrounding behavior, and lastly the positively and negativity of discourse. They study concluded that westem discourse depends on ego and individual philosophy of variable references that standing on heterogeneity and deference’s forces, and its inhabituations like deoonstruction, unfamiliarity, nihilism, and the complexity and ambiguity characteristics. The western discourse is influenced by fourth dimension, trying to maximize lormal aesthetic values by using art and concreted images. The westem discourse is intemational, scientific, utopic, abstracted inductive, methodologist, and ideologist one. The Arabic Islamic architecture discourse is depending on gathering and fixed comprehensive principles represented by culture, environment, doctrine origins, legislation, religious conceptual thoughts. The Arabic discourse depends on homogeneous and similarity forces and its inhabituations of compactness, simplicity, unity, and harmonious elements, trying to maximize spiritual forces. The Arabic Islamic discourse is speculative, critical and deductive one. To sun up this investigation the Arabic Islamic discourse is more stable, durable, and comprehensive one. And stands in apposition on westem discourse.